Anxiety and depression in patients with chronic temporomandibular pain and in controls - Giannakopoulos, Nikolaos Nikitas; Keller, Livia; Rammelsberg, Peter; Kronmüller, Klaus-Thomas; Schmitter, Marc (Journal of dentistry, 2010)
Objectives - The purpose of this study was to assess the prevalence of anxiety and depression in temporomandibular disorders (TMD) patient subgroups and in controls with or without chronic facial pain (CFP). - Methods - Our sample consisted of 61 men and 161 women. All TMD patients had suffered from pain for at least 6 months and were divided into two subgroups—an exclusively myofascial pain group and an exclusively joint pain group. Subjects without signs or symptoms of TMD but with and without CFP served as controls. All subjects were examined by calibrated examiners in accordance with the Research Diagnostic Criteria for Temporomandibular Disorders. The German version of the Hospital Anxiety and Depression Scale was used for assessment of anxiety and depression. Analysis of covariance was used to determine the effects of sex, age, and subgroup on anxiety and depression scores. Additional t-tests were performed and the subgroups were then compared with those from a general population sample. - Results - Females from the exclusively myofascial pain group were significantly more depressed than those from the general population or from the exclusively joint pain group. Male controls with CFP were significantly more depressed than female CFP controls. For anxiety, no significant effect of sex or subgroup was found. - Conclusions - Depression may play an important role in women with chronic myofascial pain whereas anxiety does not seem to be relevant for either females or males. Further anxiety screening of patients with temporomandibular pain could not be justified.
Gesehen am 09.03.2023